Action of Dicumarol on Glucosamine-1-Phosphate Acetyltransferase of GlmU and Mycobacterium tuberculosis - Han, Xiuyan; Chen, Changming; Yan, Qiulong; Jia, Liqiu; Taj, Ayaz; Ma, Yufang (Frontiers in Microbiology, 2019)
Mycobacterium tuberculosis (M. tb) is one of most pathogenic microorganism in the world. It was reported that M. tb GlmU was a potential drug target, therefore, discovering compounds targeting GlmU acetyltransferase is necessary. The nature-driven compounds were tested for inhibiting GlmU acetyltransferase activity. It was found that dicumarol exhibited inhibitory effect on GlmU acetyltransferase with the IC50 value of 4.608 μg/ml (13.7 μM). The inhibition kinetics indicated that dicumarol displayed an uncompetitive inhibition for acetyl CoA and noncompetition-competition mixed type inhibition for GlcN-1-P, respectively. The activity of dicumarol against M. tb H37Ra was evaluated with a MIC value of 6.25μg/ml (18.55μM) by alamar blue assay. The dicumarol also had inhibitory effect on several M. tb clinical sensitive strains and drug-resistant strains with the MIC value of 6.25-12.5 μg/ml (18.55-37.1 μM). Dicumarol increased the sensitivity of anti-tuberculosis drugs (isoniazid and rifampicin) when dicumarol at low concentration was present. The transcriptome and proteome data of M. tb H37Ra treated by dicumarol showed that the affected genes were associated with cell wall synthesis, DNA damage and repair, metabolic processes and signal transduction. These results provided with mechanism of dicumarol against GlmU acetyltransferase and M. tb as well. It was also suggested that dicumarol might be a potential drug for TB treatment.